Прозорі світлочутливі полімерні матеріали на основі модифікованих меламіно-формальдегідних олігомерів - Лебедєв, Володимир Володимирович; Кулініч, П. В. (НТУ "ХПІ", 2013)
В данной работе проведены исследования по синтезу модифицированных меламино-формальдегидных олигомеров высокой прозрачности и светочувствительными свойствами. Показано, что модификация толуолсульфамидом позволяет получить полимеры с коэффициентом светопропускания порядка 90 % и BAL 20-25 см.

In this paper we studied the synthesis of modified melamine-formaldehyde oligomers of high transparency and light-sensitive properties. It is shown that the modification of toluolsulfamide allows polymers with light transmission of 90 % and BAL 20-25 cm.
Transparent light-sensitive polymer materials based on modified melamine-formaldehyde oligomers
Keywords: полімерні матеріали; поліметилметакрилат; поліконденсаційні полімери; модифікатори